Exploring the Role of Social Media @asysyirkah.id in Promoting Sharia Investment among Millennial Investors: A Case Study of Asysyirkah Sharia Cooperative - Doddy Suryadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore the role of social media, particularly the @asysyirkah.id account, in promoting Islamic investment among millennial investors, with a focus on Asy-Syirkah Islamic Cooperative. Using a qualitative approach with a case study design, this research analyses how @asysyirkah.id leverages social media platforms to increase awareness, understanding, and participation in Islamic investment. Data were collected through in-depth interviews with the co-operative's social media manager, observation of social media content, and focus group discussions with co-operative members. Data analysis techniques used thematic analysis techniques. Data validity techniques used triangulation, member checking, and audit trail. The results of this study show that social media is a very effective tool for promoting sharia investment among millennials. The role of @asysyirkah.id media can increase engagement, education, and participation in sharia investment while overcoming existing challenges in content management and interaction